Tooth fragment reattachment techniques-A systematic review - Garcia, Fernanda Cristina P.; Poubel, Déborah L. N.; Almeida, Júlio César F.; Toledo, Isabela P.; Poi, Wilson R.; Guerra, Eliete N. S.; Rezende, Liliana V. M. L. (My University, 2018)
Background/Aim: Several strategies have been developed for tooth fragment reattachment following fracture. Although many techniques have been reported, there is no consensus on which one has the best results in terms of the bond strength between the fragment and the dentin over time. The aim of this study was to assess the currently reported tooth fragment reattachment techniques for fractured crowns of anterior teeth. Materials and Methods: The PubMed, LILACS, Web of Science, Cochrane, and Scopus databases were searched in October 2016, and the search was updated in February 2017. A search of the gray literature was performed in Google Scholar and OpenGrey. Reference lists of eligible studies were cross-checked to identify additional studies; gray literature and ongoing trials were investigated. Two authors assessed studies to determine inclusion and undertook data extraction. Case reports/series of three or more cases, cross-sectional studies, cohort studies, and in vivo clinical trials in all languages were included. Results: Five articles remained after screening. These studies predominantly reported on fragment reattachment with composite resin and resin cement. There was little consistency among the studies in regard to the technique used for tooth fragment reattachment and length of the follow-up period. Conclusions: According to the evidence found in the studies included in this review, simple tooth fragment reattachment was the preferred reattachment technique. An increase in the bond strength between tooth fragment and dentin was observed when an intermediate material was used. Further investigation is needed, using standard follow-up periods and larger samples.
Keywords: Crown fracture; Dental trauma; Treatment